Rancang ulang mesin penyayat daging sapi untuk bahan baku membuat abon menggunakan motor listrik 1 HP - Hasrin Hasrin; Zuhaimi Zuhaimi; Sumardi Sumardi (Politeknik Negeri Lhokseumawe, 2018)
The high consumption of processed beef products is a separate business opportunity to be developed. The shifting consumption pattern of the people in consuming processed beef products from fresh meat to processed products ready to encourage some parties to develop technology in terms of processing beef. In making abon now it is still traditional by using hands, knives or forks to cut the meat after the boiling process until cooked to be made abon. By using such manual equipment of course the process of making abon will take a long time, greater energy, and besides also slicing meat by pounding using a fork is considered less safe for workers. The purpose of this research is to get a tool / machine penyya beef is simpler for raw materials to make abon using electric motor 1 hp. Changes in the redesigned construction consist of: cylinder casing design, inlet and outlet ducts, container tubs and placemats. The result of the test has been tested by 1 kg of beef, thus showing the measured fiber texture measurement results consist of: 0.5 mm thickness, 30 mm length; 1 mm thick, 35 mm long and 1.5 mm thick, 35 mm long. Capacity of beef cultivation yields are: 3.3 ounces / minute or 1 kg / 3 minutes. So it can be concluded the closer the gaps in the cassing, then the result of the incision the better (smoother). Keywords: Meat meat machine, inlet hopper, cylinder case